The modern aspects and actual problems of the service of emergency in medicine of the republic of Karakalpakstan on prehospital stage under reforms of Uzbekistan public health system - A. K. Madreymov (Сеченовский вестник, 2014)
In the given article explored and viewed modern condition and problems of the service of emergency medicine of the Republic Karakalpakstan at organizations and rendering emergency medical help to population on system stage of the public health of Uzbekistan. Created crisis of ecological situation and its negative infl uence upon increasing of the diseases, and death-rate of the population in Aral sea region. A 12 year term of activity of the Department of fast medical help of Karakalpakstan Republic is studied and analyzed. A scientific interpreting of the explored material with the use of statistical methods and benchmark analysis is made. The recommendations are given for improvement of the service of emergency medicine in Uzbekistan.